La formació dels goigs: els testimonis renaixentistes. - BELTRAN, VICENÇ (Scripta)
In the process of the formation of goigs during the first half of the 16th century, Valencian poets seem to have played a fundamental role, dedicating themselves intensely to following in the footsteps of Bernat Fenollar. While equivalent works from the Principality, preserved in poorly maintained manuscripts, often display errors in poetic form, the Valencian production exhibits a very high technical and aesthetic standard. Thanks to their dissemination through printing, they were able to spread beyond the Kingdom of Valencia and become known throughout the Catalanspeaking territories.